2017
DOI: 10.1080/0886022x.2017.1287734
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypericum perforatum on kidney ischemia/reperfusion damage

Abstract: It has been revealed in recent studies that Hypericum Perforatum (HP) is influential on cancer, inflammatory diseases, bacterial and viral diseases, and has neuroprotective and antioxidant properties. In this study, we investigated the effect of HP, which is known to have antioxidant and anti-inflammatory effects, on kidney I/R damage. Male Sprague–Dawley rats were divided into three groups, and each of the groups had eight rats: The Control Group; the Ischemia/Reperfusion (I/R) Group; and the IR + HP Group wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
5
11
0
1
Order By: Relevance
“…The increase in pro-inflammatory cytokines may relate to the damage of renal cell structure caused by oxidative stress and lipid peroxidation. Consistently, previous studies revealed that CTX-induced nephrotoxicity resulted in the enhancement of pro-inflammatory cytokines [7,26,39]. However, numerous studies supported that inflammatory factor inhibition plays an indispensable role in the prevention of CTX-mediated renal injury [6,37].…”
Section: Discussionsupporting
confidence: 65%
“…The increase in pro-inflammatory cytokines may relate to the damage of renal cell structure caused by oxidative stress and lipid peroxidation. Consistently, previous studies revealed that CTX-induced nephrotoxicity resulted in the enhancement of pro-inflammatory cytokines [7,26,39]. However, numerous studies supported that inflammatory factor inhibition plays an indispensable role in the prevention of CTX-mediated renal injury [6,37].…”
Section: Discussionsupporting
confidence: 65%
“…Patients poisoned with paraquat may suffer multiple organ dysfunction of the heart, liver, lungs and kidney (38). BUN is an indicator that reflects kidney function, while PaCO 2 and Lac are important indexes reflecting respiratory function and lung injury (39)(40)(41). The present study hypothesized that miR-27a may be involved in kidney and lung injury in patients with MODS induced by paraquat poisoning.…”
Section: Discussionmentioning
confidence: 84%
“…The researchers determined that markers of oxidative stress and lipid peroxidation induced by hyperlipidemia were significantly decreased by systemic HP administration. Furthermore, HP treatment reduced the MDA levels and increased the SOD, CAT, and GSH-PX activity in rats with kidney ischemia/reperfusion damage [40]. In a clinical study, Naziroglu et al [41] investigated the effects of HP on oxidative stress in serum and leukocytes of patients with multiple sclerosis, and reported that the lipid peroxidation level in the HP-incubated neutrophil were markedly decreased in those patients.…”
Section: Discussionmentioning
confidence: 99%